Difference between revisions of "022 Sample Final A, Problem 3"
Jump to navigation
Jump to search
Line 10: | Line 10: | ||
|3) What special integral do we have to use? | |3) What special integral do we have to use? | ||
|- | |- | ||
− | | | + | |Answers: |
|- | |- | ||
− | |1) Since <math>x^2 - x - 12 = (x - 4)(x +3)</math> & | + | |1) Since <math style="vertical-align: -5px">x^2 - x - 12 = (x - 4)(x +3)</math> , and each term has multiplicity one, the decomposition will be of the form:  <math style="vertical-align: -15px">\frac{A}{x - 4} + \frac{B}{x + 3}</math>. |
|- | |- | ||
− | |2) After writing the equality, <math>\frac{6}{x^2 -x - 12} = \frac{A}{x - 4} + \frac{B}{x + 3}</math>, clear the denominators, and evaluate both sides at x = 4, -3 | + | |2) After writing the equality, <math style="vertical-align: -15px">\frac{6}{x^2 -x - 12} \,=\, \frac{A}{x - 4} + \frac{B}{x + 3}</math>, clear the denominators, and evaluate both sides at <math style="vertical-align: -4px">x = 4, -3</math>. Each evaluation will yield the value of one of the unknowns. |
|- | |- | ||
− | |3) We have to remember that <math>\int \frac{c}{x - a} dx = c\ln(x - a)</math> , for any numbers c, a. | + | |3) We have to remember that <math style="vertical-align: -13px">\int \frac{c}{x - a} dx = c\ln(x - a)</math> , for any numbers <math style="vertical-align: -4px">c, a</math>. |
|} | |} | ||
Line 24: | Line 24: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |First, we factor <math>x^2 - x - 12 = (x - 4)(x + 3)</math> | + | |First, we factor: <math style="vertical-align: -5px">x^2 - x - 12 = (x - 4)(x +3)</math> . |
|} | |} | ||
Line 30: | Line 30: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |Now we want to find the partial fraction expansion for <math>\frac{6}{(x - 4)(x + 3)}</math> , which will have the form <math>\frac{A}{x - 4} + {B}{x + 3}</math> | + | |Now we want to find the partial fraction expansion for <math>\frac{6}{(x - 4)(x + 3)}</math> , which will have the form <math style="vertical-align: -20px">\frac{A}{x - 4} + \frac{B}{x + 3}</math>. |
|- | |- | ||
− | |To do this we need to solve the equation <math>6 = A( x + 3) + B(x - 4)</math> | + | |To do this, we need to solve the equation  <math style="vertical-align: -5px">6 \,=\, A( x + 3) + B(x - 4)</math>. |
|- | |- | ||
− | |Plugging in -3 for x | + | |Plugging in  <math style="vertical-align: 0px">-3</math> for <math style="vertical-align: 0px">x</math>, we find that  <math style="vertical-align: -0.2px">6 \,=\, -7B</math> , and thus  <math style="vertical-align: -13px">B = -\frac{6}{7}</math> . |
|- | |- | ||
− | | | + | |Similarly, we can find <math style="vertical-align: -0px">A</math> by plugging in <math style="vertical-align: -1px">4</math> for <math style="vertical-align: 0px">x</math>. This yields <math style="vertical-align: -0.2px">6 = 7A</math> , so <math style="vertical-align: -13px">A = \frac{6}{7}</math> . |
|- | |- | ||
− | | | + | |This completes the partial fraction expansion: |
+ | ::<math>\frac{6}{x^2 -x - 12} \,=\, \frac{6}{7(x - 4)} - \frac{6}{7(x + 3)}.</math> | ||
|} | |} | ||
Line 44: | Line 45: | ||
!Step 3: | !Step 3: | ||
|- | |- | ||
− | | | + | |By the previous step, we have |
+ | ::<math>\int \frac{6}{x^2 -x -12} dx \,=\, \int \frac{6}{7(x - 4)}dx - \int \frac{6}{7(x + 3)}dx.</math> | ||
+ | |- | ||
+ | |Integrating by the rule in 'Foundations', | ||
+ | ::<math>\int \frac{6}{x^2 -x -12} dx \,=\, \frac{6}{7}\ln(x - 4) - \frac{6}{7}\ln(x + 3).</math> | ||
|} | |} | ||
Line 50: | Line 55: | ||
!Step 4: | !Step 4: | ||
|- | |- | ||
− | |Now make sure you remember to add the <math> + C</math> to the integral at the end. | + | |Now, make sure you remember to add the  <math style="vertical-align: -2px"> + C</math>  to the integral at the end. |
|} | |} | ||
Line 56: | Line 61: | ||
!Final Answer: | !Final Answer: | ||
|- | |- | ||
− | |<math>\frac{6}{7}\ln(x - 4) - \frac{6}{7}\ln(x + 3) + C</math> | + | | |
+ | ::<math>\frac{6}{7}\ln(x - 4) - \frac{6}{7}\ln(x + 3) + C.</math> | ||
|} | |} | ||
[[022_Sample Final A|'''<u>Return to Sample Final</u>''']] | [[022_Sample Final A|'''<u>Return to Sample Final</u>''']] |
Latest revision as of 18:10, 6 June 2015
Find the antiderivative:
Foundations: |
---|
1) What does the denominator factor into? What will be the form of the decomposition? |
2) How do you solve for the numerators? |
3) What special integral do we have to use? |
Answers: |
1) Since , and each term has multiplicity one, the decomposition will be of the form: . |
2) After writing the equality, , clear the denominators, and evaluate both sides at . Each evaluation will yield the value of one of the unknowns. |
3) We have to remember that , for any numbers . |
Solution:
Step 1: |
---|
First, we factor: . |
Step 2: |
---|
Now we want to find the partial fraction expansion for , which will have the form . |
To do this, we need to solve the equation . |
Plugging in for , we find that , and thus . |
Similarly, we can find by plugging in for . This yields , so . |
This completes the partial fraction expansion:
|
Step 3: |
---|
By the previous step, we have
|
Integrating by the rule in 'Foundations',
|
Step 4: |
---|
Now, make sure you remember to add the to the integral at the end. |
Final Answer: |
---|
|